Therapeutic Effect of the Correction of Vitamin D Deficiency in Patients with Benign Paroxysmal Positional Vertigo. A Randomized Clinical Trial - Mancera Sánchez, Jimena; Hernaiz Leonardo, Juan Carlos; Ishiwara Niembro, Julia Kioko; Lesser, Juan Carlos (International Archives of Otorhinolaryngology, 2022)
Introduction Benign paroxysmal positional vertigo (BPPV) appears during the same age group in which vitamin D and calcium deficiencies are evident. Vitamin D deficiency could predispose to BPPV, since these two entities share a demineralization process.Objective To establish the otological impact of vitamin D supplementation in patients with its deficiency who suffer from BPPV.Methods This was a randomized clinical trial. A total of 35 patients with vitamin D deficiency (< 30 ng/ml) and BPPV were divided into 2 groups: Group 1 (control group): treatment with repositioning maneuvers; and Group 2: treatment with repositioning maneuvers and vitamin D supplementation.Results A follow-up of between 6 and 13 months and a log rank test revealed that the probability of recurrence between the experimental groups was significantly different, with group 2 having a decreased recurrence of vertigo (p = 0.17). Scores in the Dizziness Handicap inventory (DHI) in patients treated with vitamin D supplementation were smaller (10 ± 9) when compared with a score of 36 ± 9 in the control group.Conclusion Plasmatic values of 25-hydroxyvitamin D have an impact in patients with BPPV, who present an improvement in their quality of life when their vitamin D levels are replaced with supplementation. Benign paroxysmal positional vertigo could stop being perceived as a purely otologic disease.
Keywords: benign paroxysmal positional vertigo; deficiency; vitamin D